Construction of structure bridge in Kelantan Darul Naim / Muhammad Fahmi Arifin - Arifin, Muhammad Fahmi (Universiti Teknologi MARA, Perak, 2021)
This report describes and explains my journey of internship training at PJZSB Construction within 14 weeks to fulfill the requirement for Apprenticeship. The training started from 23th August 2021 and ended on 06th January 2022 with estimated duration of 14 weeks. PJZSB Construction is a well-known construction company in Malaysia originally known as Pembinaan Jaya Zira Sdn Bhd (PJZSB). The internship training was located in Gua Musang Street, Kelantan. During internship training, I experienced new tasks, work cultures and values in Public Relations and Corporate Communication. This is the first time I experienced real hands-on working environment since both Public Relations and Corporate Communication are quite different from what I studied. Initially, I felt difficult and challenging to adapt with the new environment and the work nature, but eventually I managed to adapt and keep learning from my fellow colleague at PJZSB Construction. While completing the internship, some of my ideas were rejected and some were modified and these experiences helps me to improve myself better and prevent from repeating the same mistakes. My supervisors always give constructive whenever I did some mistakes and I found that it is quite helpful for me to learn and adapt with the new environment. I learned that as a human being; it is normal to make mistakes but somehow we can avoid the mistakes from happening twice by following the procedures. Other than that, the internship program exposed me on how the company runs which is totally different from what being taught in the classroom. I faced with shorter due dates during the internship training which helps me increase my work productivity and critical thinking when creating a new content or completing the task given. Moreover, I’m able to improve my self-confidence and responsibilities towards the task given during the internship period. This can be considered as a preparation for me before starting my future career path. In a nutshell, I believe that this Integrated Internship Program at PJZSB Construction provides me with various work experiences, work cultures and work values which is crucial for me to begin with my future career path. By completing the internship training I believe that this program helps the student in adapting and preparing with the real working environment; despite of the MCO announcement and the SOPs given by the government throughout the training session. I also learned that students should prepare themselves better in language proficiency especially in Bahasa Malaysia and English to strengthen oral presentation and writing skills.